Edukasi dan Praktik Cuci Tangan Enam Langkah Menggunakan Sabun dan Air Mengalir sebagai Upaya Preventif Mencegah Kecacingan pada Anak Sekolah dan Prasekolah - Riswi Alinda Fatmawati (Universitas Sebelas Maret, 2023)
Background: Helminthiasis are an infectious disease that is common in tropical andsubtropical regions. Worms are still one of the problems faced by several countries in the world, including Indonesia. Recorded 100,6 million pre preschool-aged children (pre-SAC) and 400 million school-aged children (SAC) in the world were treated for soil-transmitted helminthiasis (WHO, 2021). As for Indonesia, the only country in the South-East Asia Region that is endemic for schistosomiasis, reported treatment of 159 individuals (SAC and adults) in 2021, for a coverage rate of 0.5%. The high prevalence of helminthiasis indicates the need to provide education to children regarding preventive measures to prevent helminthiasis. One of the preventive measures is to diligently wash your hands in the six steps with soap and running water.Methods: The method of implementing community service includes the preparation,implementation, and evaluation stages.Results: The activity was carried out on December 4, 2022 at the house of a resident of RT 04 RW 04, Timuran. During the provision of education and practice, the children looked enthusiastic in answering and following the directions.Conclusion: Community service by providing education and hand washing practices has a significant impact on children's attitudes and knowledge.Keywords: hand washing, community service, helminthiasis, children, preventive